A typology of mentally disordered firesetters - Harris, G. T. (Journal of interpersonal violence, 1996)
Cluster analytic techniques were used to develop a typology of mentally disordered male firesetters and the fires they set. Childhood variables, adult correctional and psychiatric variables, and characteristics of their index fires were used to assign the 243 men to one of four subtypes: psychotics, underassertives, multi-firesetters, and criminals. The subtypes differed on many clinical characteristics and in their likelihood of firesetting, violent, and nonviolent recidivism. Implications for risk prediction and treatment are discussed